Corrigendum to Acceptance of Construction Scheduling Visualizations: Bar-charts, Flowline-charts, Or Perhaps BIM?: Procedia Engineering volume 164, pages 558–566. (2016) - Nordahl-Rolfsen, Christian; Merschbrock, Christoph
Abstract : All authors agree that the BSc students, on whose work this article is based, deserve more credit. Our students did a great job. Thus, they should be moved from the acknowledgement section to the authorship line, which would have been good practice in the first place. The new authorship line is: Cathrine Høglo Stenberg a, Hanne Pretorius Smeby a, Lars Marius Brovold Skaug a, Christian Nordahl Rolfsen a, Christoph Merschbrock a a Oslo and Akershus University College, P.O. Box 4, St. Olavs plass, NO-0130 Oslo, Norway The authors would like to apologise for any inconvenience caused.